ON A NEW SPECIES OF GENUS SCARDAMIA GUENEE (SUBFAMILY : BOARMINAE) - WALIA, V.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1994)
Scardania easwarammae sp. nov. has been described in detail and a key to the three Indian species is given.